Use of Gold Nanoparticles in Diagnostics, Surgery and Medicine: A Review (Bangladesh Journal of Medical Biochemistry, 2013)
Noble metals and their compounds have a long and distinguished history as therapeutic agents in medicine. Recent years have seen tremendous progress in the design and study of nanomaterials geared towards biological and biomedical applications. Particularly gold nanoparticles have attracted intensive interest, because they are easily prepared, have low toxicity and can be readily attached to molecules of biological interest. The gold nanoparticles have become more precious than pretty gold because of their wide use and applications. The present article gave a critical review of the wide applications and uses of gold nanoparticles in diagnostics, surgery and medicine. DOI: http://dx.doi.org/10.3329/bjmb.v5i2.13346 Bangladesh J Med Biochem 2012; 5(2): 56-60